Effect of Work Environment on Employee Performance at PT. PLN (Persero) Punagaya Power Plant Implementing Uni in Jeneponto District - Agusni. S; Agung Widhi Kurniawan; Zainal Ruma; Romansyah Sahabuddin; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
The purpose of this study is to test whether the work environment variables have an influence on employee performance at PT. PLN (Persero) UPK Punagaya. The independent variable in this study is the work environment while the dependent variable is employee performance. The research was conducted using a survey method, in which data was obtained by distributing questionnaires to 57 respondents. The population in this study are employees at PT. PLN (Persero) UPK Punagaya in Jeneponto Regency, the sampling method used is simple random sampling. The collected data were analyzed using a simple linear regression equation. From the results of the simple linear regression analysis test, the following formula can be obtained Y = 29.006 + 0.129X while the coefficient of determination R2/R Square = 0.077 means that the work environment variable has an effect of 77% on employee performance. While the rest is influenced by other factors. Partial test results for X obtained Tcount > Ttabel (2.142 > 0.67906) with a significance of 0.000, then H1 is accepted and H0 is rejected. From the results of this study, it can be concluded that the work environment is a very important thing to pay attention to the management of PT. PNL (Persero) Puangaya UPK in Jenepont district, the better the work environment that is implemented, the better the performance of employees at PT. PLN (Persero) UPK Punagaya in Jeneponto Regency.